2016
DOI: 10.1016/j.rmb.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of some rodents (Cricetidae, Heteromyidae, and Sciuridae) from Zacatecas, Mexico

Abstract: Eighty-six specimens representing 7 species of rodents from 9 localities in the state Zacatecas were examined for helminths. Only 5 host species were found to harbor at least 1 species: Chaetodipus sp., Dipodomys merriami atronasus, Neotoma mexicana, Otospermophilus variegatus, and Peromyscus sp.; in contrast Mus musculus and Reithrodontomys sp., were not parasitized. Three species of cestodes (Catenotaeniidae gen. sp., Hymenolepis sp., and Raillietina sp.) and 7 nematodes (Gongylonema sp., Heteromyoxyuris lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“… Dallas and Presley (2014) and Cardoso et al (2020) also demonstrated that host attributes (e.g., body mass and trophic status or diet) were important factors related to the distribution of helminths of rodents. Similarly, Martínez-Salazar et al (2016) suggested that the presence of rodents with different diet types contributed to the observed helminth diversity, given the occurrence of species with direct and indirect life cycles. In the present study, the presence of hosts with Frugivore/Granivore, Frugivore/Omnivore, Frugivore/Seed and Insectivore/Omnivore diets influenced the diversity of helminths.…”
Section: Discussionmentioning
confidence: 97%
“… Dallas and Presley (2014) and Cardoso et al (2020) also demonstrated that host attributes (e.g., body mass and trophic status or diet) were important factors related to the distribution of helminths of rodents. Similarly, Martínez-Salazar et al (2016) suggested that the presence of rodents with different diet types contributed to the observed helminth diversity, given the occurrence of species with direct and indirect life cycles. In the present study, the presence of hosts with Frugivore/Granivore, Frugivore/Omnivore, Frugivore/Seed and Insectivore/Omnivore diets influenced the diversity of helminths.…”
Section: Discussionmentioning
confidence: 97%
“…The present work represents the first record of a cestode parasitizing a squirrel species in México. Previous to our report, only 10 nematode taxa had been recorded from -Prieto et al 2012;Martínez-Salazar et al 2016). This study increases to 11 the total number of helminth species known from squirrels in México.…”
Section: Introductionmentioning
confidence: 47%
“…In Mexico, unidentified species of Hymenolepis have been reported from other heteromyid rodents such as H. irroratus in Puebla and Queretaro (García-Prieto et al 2012) and Dipodomys merriami Mearns in Zacatecas (Martínez-Salazar et al 2016). This is the first record of Hymenolepis in H. gaumeri.…”
Section: Site Of Infection: Small Intestinementioning
confidence: 74%
“…Between 2001 and 2018, Campeche, Quintana Roo and Yucatan lost approximately 1.5 million hectares of tree cover mostly due to cattle production systems and agriculture (Global Forest Watch 2020). Deforestation and fragmentation have had a significant impact on the distribution and diversity of mammals in Mexico (Sánchez-Cordero et al 2009), being increasingly threatened along with the helminths they harbor (Martínez-Salazar et al 2016) and also changing the patterns of parasite infections (Bordes et al 2015). Rodents account for approximately 39% of mammal species worldwide (Burgin et al 2018).…”
Section: Introductionmentioning
confidence: 99%